On the relationship between physical activity, physical fitness, and stress reactivity to a real-life mental stressor - Gnam, Jens-Peter; Engel, Florian (International journal of stress management, 2019)
Laboratory studies confirm physical activity and physical fitness to be protective factors against mental stressors. However, there is still little evidence on the transferability of these findings into real-life stress situations. The main aim of this study was to examine the impact of physical activity and physical fitness on real-life psychophysiological stress responses to a mental stressor. The final exam of a training course for firefighter incident commanders represented the real-life mental stressor of our study. Cortisol level, heart rate, and heart rate variability were measured in 48 male firefighters at rest and during the exam. Cognitive stress appraisal was assessed as a psychological stress indicator. Physical activity was estimated using the International Physical Activity Questionnaire. Maximal oxygen uptake was measured as a parameter for physical fitness. The participants were divided according to their level of physical activity and physical fitness into groups of lower and higher physical activity/fitness level. All subjects showed significant physiological stress responses and a moderate cognitive stress appraisal during the exam. Subjects with different physical activity and physical fitness levels did not differ significantly in their physiological stress responses. Cognitive stress appraisal seemed not to be influenced by physical fitness but by physical activity, as more active subjects experienced significantly higher stress levels. Cognitive stress appraisal did not predict physiological stress responses. The assumed stress-buffering effect of physical activity and physical fitness could not be observed during the real-life mental stress of an exam consisting of commanding a group of firefighters in an emergency simulation. (PsycINFO Database Record (c) 2019 APA, all rights reserved)